5b+(11-3b)+23=

Simple and best practice solution for 5b+(11-3b)+23= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b+(11-3b)+23= equation:


Simplifying
5b + (11 + -3b) + 23 = 0

Remove parenthesis around (11 + -3b)
5b + 11 + -3b + 23 = 0

Reorder the terms:
11 + 23 + 5b + -3b = 0

Combine like terms: 11 + 23 = 34
34 + 5b + -3b = 0

Combine like terms: 5b + -3b = 2b
34 + 2b = 0

Solving
34 + 2b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-34' to each side of the equation.
34 + -34 + 2b = 0 + -34

Combine like terms: 34 + -34 = 0
0 + 2b = 0 + -34
2b = 0 + -34

Combine like terms: 0 + -34 = -34
2b = -34

Divide each side by '2'.
b = -17

Simplifying
b = -17

See similar equations:

| 15r*2+32r-7=0 | | -8+-13= | | 5z+6-2z=51-2z | | x^2+4x^2+36x^2=4x^2+16x^2 | | -2n=-18 | | x^3+5X-3=0 | | -12+4x=7(2x+4) | | 3(5x-6)+7(10-x)= | | x^2+2x^2+6x^2=2x^2+4x^2 | | 3n+7(1+4n)=37+n | | 4.3q-2.8-5.8q=0.5q-2.8 | | -3(y-4y)+6=-4(2y-y)+4+12y | | 4x^2+24x^2+36x^2=4x^2+16x+16 | | 35x^7+25x^5+15x^3= | | 120/55=45.6/a | | -10-8x=7+3(x+1) | | -2=3y-18-55y | | 4x^4-75xy^3=0 | | 4x^2+25x^5+26x^4=4x^2+16x+16 | | x^2+6x-4= | | 30y^3+84y+120y^2= | | 2y^2-13y+20=0 | | 4(x)-8(x+1)=8 | | 4x-14=6(x-3) | | 13-2/9x=9 | | (x^3+x^2+2x-4)/(x-1) | | -15+x=x+20 | | x^2+24x+36=36x+81 | | 5(a-7)+10=3(a-5) | | -10x-19=19+-8x | | (1/5)-(1/4) | | 31+x=3(5+3x) |

Equations solver categories